THE EFFECT OF INSTRUCTIONAL DESIGN OF ENGLISH SUBJECT BASEDONCOMPONENTDISPLAYTHEORYONSTUDENTS’ ACHIEVEMENT - Mulyadi Na (Akademika : Jurnal Teknologi Pendidikan, 2016)
This study constitutes an attempt to apply the Component Display Theory (CDT) as a knowledgebaseondesigningwritteninstruction.Itaimstoinvestigatetheeffectof“secondarypresentation”on;(1)students’overallachievement,(2)thelearningtargets:rememberconcept,anduseconcept. CDTrefers to two dimensions of instructional objectives and provides “primary” and “secondarypresentations.”The“primarypresentation”reflectsthemaininstructionalmessagescomprisingfourcomponents of presentation strategies based on the depth and the method of presentation. The“secondary presentation” elaborates the “primary presentation” to make it easier for learners toreceive, process, and record the information. CDT postulates that for every instructional objective thereis a combination of instructionalstrategycomponentsof“primary”and“secondarypresentations”that effectively strive for the achievement of the learning objectives. The study limits its scope to the useof(1)“primarypresentation”consistingofrules,examples,recall,andpractice,and(2)“primarypresentation”with“secondarypresentation”consistingofrules,examples,recall,practice,andgivingintroduction and feedback.The population of this study are second year students of Public Junior High School in Bekasi.The sample consists of 342 respondents, selected by random sampling. Quantitative analysis usingAnalysis of Covariance (ANCOVA) was used to analyse data. Multiple choice questions test was usedtomeasurethestudents’achievement.The ANCOVA analysis finding showed; (1) students taught using “primary presentation”togetherwith“secondarypresentation”obtainedhighermeangainscoresonoverallachievementthan those taught using “primary presentation” only, and (2) the addition of the secondarypresentationincreasesstudents’achievementonlearningtargetsofrememberconcept and use concept